Does the Marginal Hospitalization Save Lives? The Case of Respiratory Admissions for the Elderly - Janet Currie; David Slusky (Institute of Labor Economics (IZA), 2020)
Some commentators estimate that up to a third of U.S. medical spending may be wasted. This study focuses on the decision to hospitalize elderly Medicare patients who present at the emergency room (ER) with respiratory conditions. Failing to hospitalize sick patients could have dire consequences. However, in addition to generating higher costs, unnecessary hospitalization puts patients at risk of hospital acquired conditions and disrupts their lives. We use variation in the patient's nearest hospital's propensity to admit patients with similar observable characteristics as an instrument for the admission decision. While OLS estimates suggest that admitted patients are more likely to die, when we instrument for patient admission we find that the marginal hospital admission increases the number of hospital days by seven days and increases charges by 42,000 but has no effect on the risk of death in the course of the next year. The marginal hospitalization also reduces the risk of another emergency department visit in the next 30 days but increases outpatient visits over the same time horizon with no overall impact on charges. Longer term effects also include increased outpatient visits but effects on patient costs and health outcomes over the next year are minimal. Overall, these results lend support to the argument that in many cases the marginal hospitalization is unnecessary.
Keywords: I1; 330; respiratory emergency; hospital admission